Perancangan Alternatif Penawaran Plan Small Medium Enterprise Menggunakan Pegasystems 7 (Studi Kasus : PT. Asuransi Sinarmas) - Revian Palpialy; Radius Tanone (Jurnal Teknik Informatika dan Sistem Informasi, 2018)
PT. Asuransi Sinarmas is a company that provides insurance services with various products offered. One of them is Small Medium Enterprise (SME) which is a part of Produk Simas Sehat Corporate (SSC) that guarantees small-scale companies to ensure the well-being of their employees and their families in the health sector with a predetermined premium value. Misinformation about good warranties, plans, total value of premiums and benefits that can occur can affect the value of an insurance product to a customer. The purpose of this study is to assist the broker or marketing company in offering SME insurance products to prospective customers through calculation of premiums based on the selected collateral and minimize the occurrence of incorrect data input and calculation of premium SME. This application is built using Pegasystem 7 and the method used is Research and Development (R & D). System testing is done by black-box testing method and analysis of test result based on User Acceptance Testing (UAT). So the conclusions obtained from this study is the application can run as expected because it can be a means to help brokers provide information related to the company's health insurance products. Information provided about insurance covered by insurance companies to SME category companies wishing to become customers of this insurance product.